O Ídolo à luz das novelas policiárias de Fernando Pessoa - Schincariol, Marcelo (Pessoa Plural)
The broader goal of this article is to offer a possible answer to the apparent absence of authorship marks in scripts for films written by Fernando Pessoa. Focusing on “Note for a thriller, or film”, adapted by director Pedro Varela in O Ídolo, a 2021 short film, I present an analysis in which scripts and realized version are approached in dialogue with the detective fiction theorized and practiced by Fernando Pessoa.